ChemInform Abstract: Absolute Configuration and Antibiotic Activity of Neosartorin (I) from the Endophytic Fungus Aspergillus fumigatiaffinis. Issue 28 (15th July 2014) - Ola, Antonius R. B.; Debbab, Abdessamad; Aly, Amal H.; Mandi, Attila; Zerfass, Ilka; Hamacher, Alexandra; Kassack, Matthias U.; Broetz‐Oesterhelt, Heike; Kurtan, Tibor; Proksch, Peter
Abstract The title compound (I) exhibits substantial antibacterial activity against a broad spectrum of Gram‐positive bacterial species (e.g. staphylococci, streptococci, enterococci, B.